Is air pollution negatively associated with physical fitness?—A cross-sectional study in 174,246 Chinese students - Weixin Chen; Jiaming Yan; Zhenxing Kong; Yuliang Sun; Wenfei Zhu; Jie Kang (PLoS ONE, 2025)
Objectives Air quality in China has become an increasing concern, its association with physical fitness remains unclear. This study represents one of the largest nationwide investigations of this association, leveraging data from 174,246 students aged 7–22 years across 30 provinces. Methods Annual concentrations of PM₂.₅, PM₁₀, SO₂, NO₂, CO, O₃, and the Air Quality Index (AQI) were obtained from the Tracking of Atmospheric Pollution in China dataset. Physical fitness was evaluated through a comprehensive set of field-based tests covering anthropometric, cardiopulmonary, flexibility, muscular strength, and endurance. Associations were examined using generalized linear models with progressive adjustments: Model 1 controlled for demographic factors (age, sex, residence, province), Model 2 additionally accounted for physical activity and parental factors, and Model 3 further incorporated temperature and humidity. Results After adjusting for covariates, each 1 μg/m³ increase in PM₂.₅ and PM₁₀ was associated with decreases in physical fitness scores of 0.18 [95% CI: −0.22, −0.14] and 0.12 [−0.16, −0.08] points, respectively. SO₂, O₃, and CO showed similar negative associations, with reductions of 0.42 [−0.47, −0.38], 0.21 [−0.25, −0.16], and 0.16 [−0.20, −0.11] points, respectively. In contrast, NO₂ exhibited a positive association, with an increase of 0.29 [0.25, 0.33] points per 1 μg/m³. AQI was also inversely related to fitness, decreasing scores by 0.17 [−0.21, −0.13] points per 1-unit increase. Conclusions Ambient air pollution is adversely associated with physical fitness among Chinese children, adolescents, and young adults, highlighting the importance of air quality improvement strategies for youth health. Future longitudinal studies are warranted to strengthen causal inference.